Analisis Strategi Pemasaran dalam Menarik Minat Beli Konsumen pada Toko Moondo Home Baked and Kitchen di Kota Bukittinggi - Dean Permata Rizki; Septria Susanti (ARZUSIN, 2026)
The culinary industry, particularly the bakery and pastry sector, has received attention in several previous studies; however, studies that specifically examine the transition from online to offline sales systems and its impact on marketing strategies and consumer purchase intention remain limited. This study aimed to analyze marketing strategies for attracting consumer purchase intention at Toko Moondo Home Baked and Kitchen. This study used a qualitative approach with a descriptive design. The research informants consisted of the business owner as the main informant and consumers as supporting informants selected through purposive sampling. Data were collected through observation, interviews, and documentation, and were then analyzed using the stages of data reduction, data display, and conclusion drawing. The results showed sales fluctuations and differences in consumer characteristics between online and offline systems, namely that online consumers focused more on product visuals, whereas offline consumers placed greater consideration on price. In addition, marketing strategies had not been implemented optimally, particularly in the aspects of branding, business location, and digital promotion. Nevertheless, elements of the marketing mix, such as product, price, service, process, and payment methods, had been implemented well. These findings contribute to the development of studies on consumer behavior-based marketing strategies and expand understanding of the marketing dynamics of culinary MSMEs. The conclusion of this study emphasizes the importance of optimizing marketing strategies in accordance with consumer characteristics, particularly through strengthening branding and utilizing digital media, with practical implications for MSME actors in increasing consumer purchase intention.